Experience instead of Event: Changes in Open-Air Museums Post-Coronavirus - Roeland Paardekooper (EXARC, 2020)
An EXARC 'call to arms' to reevaluate and develop your Open-Air Museum's interpretation strategy. The year 2020 started out for museums as usual, with plans for new exhibitions, new buildings even, and above all many events and visitors. Soon we saw how wrong we were. Open-air museums who had prepared to open up for the season found out that COVID-19 meant they were sitting ducks: no visitors, no income, no life in the museum area. The situation will not return to 'normal', we will have to think again about everything we were used to in our work. This article is an EXARC 'call to arms' to reevaluate and develop your Open-Air Museum's interpretation strategy.